(а-1)x^2+(a+4)x-(a+3)=0 A = a - 1 B = a + 4 C = -(a + 3) 1) А = 0 => 1 корень 2)A не равно 0 => а не равно 1 1) В = 0 => a = -4 -5x^2 + 2 = 0 x^2 = 2/5 2 различных корня 2) С = 0 => a = -3 -4x^2 + x = 0 x(1 - 4x) = 0 2 различных корня 3) В не равно 0 => а не равно -4 С не равно 0=> а не равно -3 (а-1)x^2+(a+4)x-(a+3)=0 D = (a+4)^2 + 4(a-1)(a+3) = a^2 + 8a + 16 + 4a^2 + 8a - 3 = 5a^2 + 16a + 13 >0 D1 = 64 - 260 < 0 => нет таких а ответ: при а = -4 => 2 корня при а = -3 => 2 корня
(а-1)x^2+(a+4)x-(a+3)=0 A = a - 1 B = a + 4 C = -(a + 3) 1) А = 0 => 1 корень 2)A не равно 0 => а не равно 1 1) В = 0 => a = -4 -5x^2 + 2 = 0 x^2 = 2/5 2 различных корня 2) С = 0 => a = -3 -4x^2 + x = 0 x(1 - 4x) = 0 2 различных корня 3) В не равно 0 => а не равно -4 С не равно 0=> а не равно -3 (а-1)x^2+(a+4)x-(a+3)=0 D = (a+4)^2 + 4(a-1)(a+3) = a^2 + 8a + 16 + 4a^2 + 8a - 3 = 5a^2 + 16a + 13 >0 D1 = 64 - 260 < 0 => нет таких а ответ: при а = -4 => 2 корня при а = -3 => 2 корня
2)27a³-16,2a²b+3,24ab²-0,216b³
3)0,001m³-0,12m²n+4,8mn²-64n³
4)0,125a³+0,12a²b+0,0384ab²+0,004096
1)a³+6a²b+12ab²+8b³
2)x³-9x²y+27xy²-27y³
3)8m³-36m²n+54mn²-27n³